Violence and Disability: Experiences and Perceptions of Victimization Among Deaf People - Admire, Amanda (Journal of interpersonal violence, 2021)
Research on the unique experiences of deaf people is rare, and limited information exists regarding the nature and extent of violence against this population. Existing scholarship highlights the increased vulnerabilities of deaf individuals; however, there remains a paucity of research that examines how deaf and hard of hearing individuals perceive their own victimization. Also lacking is research on the experiences of deaf individuals outside of the United States, where cultural norms and the status of the deaf may be quite different. In this article, we examine the relationship between violence and disability among 60 deaf people from developing countries. Each respondent is seeking legal asylum in the United States, and their asylum depositions provide the data for analysis. Thematic analyses reveal that deaf individuals experience abuse and violence within various social institutions and draw upon social perceptions of disability to explain their negative treatment. Notably, respondents cite their status as “devalued persons” as the driving factor behind institutional and interpersonal experiences of violence and, in some cases, respondents internalize this devalued status. The results suggest social conceptualizations of disability and deafness are important to consider in the context of violence and abuse.